Distinguished educators on reading contributions that have shaped effective literacy instruction - Padak, Nancy (International Reading Association, 2000)
"Delve into the works of the field?s leading scholars. The editors of The Reading Teacher from 1989 to 1999 compiled the articles in this collection from the journal?s Distinguished Educator series. They then invited all authors to contribute an autobiography and update their original pieces. The result is a rich collection of scholarly thinking that has guided literacy instruction into the 21st century."--Publisher's description.